Factors determining the range of motion in primary total knee arthroplasty - Rathod, Mallesh; Kanugula, Sandeep Kumar; S. M., Venugopal; Gudaru, Jagadeesh (International Journal of Research in Orthopaedics, 2019)
Background: Total knee arthroplasty (TKA) is one of the most successful surgical procedure with over 90% survival rate at 10 to 15 years. It provides a stable, pain free range of motion (ROM) for day to day activities. The aim of this study is to evaluate various factors determining ROM after TKA. Methods: 348 patients with 390 knees treated with TKA using cruciate retaining (CR) and posterior stabilized (PS) prosthesis were included and analysed. Mean follow up period was 18 months. Patients were analysed for factors like age, sex, diagnosis, body mass index (BMI), pre-operative exercises, ROM, deformity, posterior femoral condylar offset (PFCO), posterior tibial slope (PTS), post-operative rehabilitation and implant design (CR vs PS). Statistical analysis of above factors on knee ROM was done. Patients were assessed pre-operatively, at 6 weeks, 3, 6, 12 and 18 months post-operatively. Results: Age and sex did not affect the final ROM. The mean knee ROM improved from 86.87° to 96.95°. Factors like BMI, deformity had negative correlation and Pre-operative diagnosis, exercises, knee scores, good preoperative ROM, PFCO, PTS had positive correlation on ROM. Conclusions: Pre-operative exercises, diagnosis, ROM, deformity, BMI, PFCO and PTS were important factors which influence ROM in TKA. Patient selection and preoperative counselling are important for good clinical outcome.